Occurrence in Japan of Frankliniella hemerocallis (Thysanoptera, Thripidae), with description of the larva and key to Frankliniella species from Japan - Masumoto, Masami; Okajima, Shuji (Zootaxa, 2013)
The occurrence in Japan of the daylily thrips, Frankliniella hemerocallis, is confirmed. This thrips probably originated in Asia or Eurasia, because it is highly specific to Hemerocallis [Liliaceae] which is native to these areas. This thrips feeds on leaf, stem and petals rather than pollen. The second instar larva is described, and a key provided to the adults of Frankliniella species recorded from Japan.